(untitled) (Zaporizhzhia Historical Review, 2021)
The article describes the life and activity of colonel of the Novoslobidsciy cossack regiment Nikolay Adаbash. Although N.Adаbash was not ukrainian by an origin, and was besides appointed on position of colonel by Russian power, he was able to extract respect and authority among novoslobidsciy cossacks, as tried to defend interests of the Novoslobidsciy regiment from encroachments of novoserbians.